Management and Outcome of Parathyroid Carcinoma-Induced Primary Hyperparathyroidism: A Single-Centre Experience - Loredana De Pasquale; Antonio Mario Bulfamante; Giovanni Felisati; Luca Castellani; Giorgio Ghilardi; Alberto Maria Saibene (International Journal of Endocrinology)
Background. Parathyroid carcinoma (PC) is the rarest endocrine cancer and an infrequent cause of primary hyperparathyroidism (PHPT), responsible for less than 1% of cases. Due to its rarity, treatment is challenging. Methods. A retrospective cohort study on 462 patients referred for parathyroidectomy to Thyroid and Parathyroid Unit at Santi Paolo e Carlo Hospital, Milan, Italy, from 2011 to 2021. We identified and individually described the patients affected with PC. Then, we split all patients treated for PHPT into four groups based on the cause: PC, adenoma, atypical adenoma, and hyperplasia. Patients’ demographics, preoperative evaluation results, intraoperative findings, and outcomes for the PC group were compared with groups of PHPT due to benign causes. Results. Eight cases of PC were identified, five males and three females. Seven cases presented with symptoms of hypercalcemia and one with a neck mass. Five underwent en bloc resections and three local excisions. Histopathological features showed capsular invasion in four patients, capsular and soft tissue invasion in three patients, and vascular invasion in one case. No patients had distant metastasis. One patient was classed as high risk based on the Schulte classification system. All patients treated for PC were alive and disease-free at a mean follow-up of 38.4 months. When compared with other PHPT patients, PC patients were more frequently male and had higher preoperative blood calcium and PTH and lower phosphate levels, larger and heavier parathyroids excised, lower postoperative calcium, and a higher rate of postoperative hypoparathyroidism. Conclusion. Our study highlights some aspects valuable to suspect PC and differentiate PHPT-PC from benign causes of PHPT preoperatively. Preoperative suspicion of malignancy is essential to guarantee the best course of treatment for patients. Although limited for size and follow-up, the excellent outcome of our series seems to support the value of both surgery extension and risk class according to the Schulte classification as possible prognostic factors for recurrence.